2017
DOI: 10.1016/j.cub.2017.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Activation of a Plant NLR Complex through Heteromeric Association with an Autoimmune Risk Variant of Another NLR

Abstract: SummaryWhen independently evolved immune receptor variants meet in hybrid plants, they can activate immune signaling in the absence of non-self recognition. Such autoimmune risk alleles have recurrently evolved at the DANGEROUS MIX2 (DM2) nucleotide-binding domain and leucine-rich repeat (NLR)-encoding locus in A. thaliana. One of these activates signaling in the presence of a particular variant encoded at another NLR locus, DM1. We show that the risk variants of DM1 and DM2d NLRs signal through the same pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(85 citation statements)
references
References 56 publications
3
82
0
Order By: Relevance
“…Certain conventional NLRs work as heteromeric pairs, through interacting N-terminal domains (Césari et al, 2014;Tran et al, 2017;Williams et al, 2014). RPP7 proteins are canonical CNLs, while RPW8/HR proteins are non-NLR, CCR-only proteins.…”
Section: Rpp7b Oligomerization Induced By Association With Hr4 Fei-0mentioning
confidence: 99%
“…Certain conventional NLRs work as heteromeric pairs, through interacting N-terminal domains (Césari et al, 2014;Tran et al, 2017;Williams et al, 2014). RPP7 proteins are canonical CNLs, while RPW8/HR proteins are non-NLR, CCR-only proteins.…”
Section: Rpp7b Oligomerization Induced By Association With Hr4 Fei-0mentioning
confidence: 99%
“…Such a mode of action would have enabled massive duplication and functional diversification without accumulation of deleterious effects. Interestingly, recent studies have shown that mismatched NLRs, which probably operate through positive regulation, trigger autoimmunity leading to hybrid necrosis, adding another layer of complexity in NLR evolution (43,45). Future studies on how NRC and NRC-dependent NLR proteins function should shed light on the mechanistic detail of how this NRC network mediates immune responses and disease resistance.…”
Section: Nrc2 Nrc3 and Nrc4 Redundantly Contribute To Rx-mediatedmentioning
confidence: 99%
“…Such incompatibilities between independently evolved NLRs have been described in Arabidopsis; DM1 and DM2d are two TNLs from two different Arabidopsis ecotypes, Uk‐3 and Uk‐1, and underlie hybrid necrosis observed in F1 progeny. The necrosis results from incompatibility between these two TNLs that triggers the auto‐activation of immune responses (Chae et al ., ; Tran et al ., ). Similarly, earlier work in Arabidopsis has also established NLR incompatibility as the basis for hybrid necrosis (Bomblies et al ., ).…”
Section: Regulation At the Protein Levelmentioning
confidence: 97%